Managerial Recommendations Improving the Competitive Capability of Firms Based on Total Quality Management during Covid-19 Pandemic - Ha Van Son; Nguyen Van Trai; Phan Thanh Tam (Emerging Science Journal, 2022)
In 2021, the COVID-19 epidemic affected many aspects of the provinces' socio-economic fields, especially deeply affecting businesses at enterprises. The task of ensuring social security continues with the management agencies, who need appropriate solutions and support policies to encourage and help enterprises return to production and trade after the quarantine society quickly. The basis for management theory has contributed to improving the competitive capability based on improving Total Quality Management (TQM), such as the "just in time" system. TQM aims to enhance the quality of products and satisfy customers to the best extent possible. The distinguishing feature of TQM from previous quality management methods is that it provides a comprehensive system for managing and improving all aspects related to quality and involves the participation of the public, every department, and every individual to achieve the set quality goals. The article's novelty identifies factors influencing total quality management and competitive capability of firms in Vietnam with one percent significance. Methods: The authors surveyed 650 managers at many enterprises in Vietnam. And the authors used a convenient sampling method. SPSS tools processed 589 samples to measure Cronbach's alpha, exploratory factor analysis (EFA), confirmation factor analysis (CFA), and test structural equation modeling (SEM). The authors proposed several recommendations to enhance the total quality management and competitive capability of firms. Doi: 10.28991/ESJ-2022-06-03-010 Full Text: PDF